An urban sensing system as backbone of smart cities. - Allbach, Benjamin; Henninger, Sascha; Deitche, Eugen (My University, 2014)
A complex urban ecosystem, with various local climate and air quality influences, emerges within urban structures with interacting anthropogenic and natural factors. These influences have different temporal and spatial characteristics. Human well-being is influenced by a multitude of microclimatic effects, which are elementary for urban planning. These form the basis of intelligent control and design of various processes within urban smart cities. For example, micro climatic modeling helps to get a better understanding of temperature changes in diverse urban areas. Possible consequences of different planning scenarios can be explored in advance. The required data for such scenarios are mainly collected at selected locations by multiple individuals. However, the collection of the complete urban data is expensive and time consuming. The non-standardization of data saving formats and measurement procedures leads to various deviations. In future, all relevant data of a smart city should be available ubiquitously and in real time. The aim of this paper is to present a possibility of data standardization and data saving in a worldwide accessible data base. Furthermore, it should be addressed how the data base has to be structured, where local climate data can be saved, and how the data can be made accessible. The basis for this system consists of the interface between the database and different measurement instruments, whose values are stored directly in this data base. For this reason, the data base is essential for the central data infrastructure of smart cities. In addition, this paper shows how a freely accessible system not only improves the quality of urban life, but also makes it measureable.
Keywords: Stadtplanung; Stadtraum; Stadtökologie; Stadtklima; Informationssystem; Datenerfassung; Planungsinstrument; Planungsgrundlage; Klimadaten; Smart City